O uso inadequado de métodos contraceptivos como fator predisponente à gravidez na adolescência: um recorte no semiárido brasileiro - Soriano, Luzia Carla de Souza (Universidade Federal Rural do Semi-Árido, 2020)
Adolescence is a period of life marked by physical, psychological and social changes in which the individual becomes vulnerable to external and internal elements that mold behavior and personality, The brazilian Statue of the Child and the Adolescent considers autonomy and access to integral health, including sexual and reproductive health, as rights of the adolescent. Sexual education for the teenagers impacts in the development of a healty sexual life and in correct use of contraceptives, seems to be the main key for prevention of unwanted pregnancy in adolescence, an event that impacts directly in health, social relationships and future perspectives for women. This is a transversal exploratory research that took place in Mossoró, Rio Grande do Norte, from May to November 2019, involving 32 volunteers that answered a questionary.The information was analyzed using simple statistics in the program Excel. The study shows that adolescents know contraceptive methods, but still have poor knowledge of the correct use of them, consequently developing unwanted pregnancy.
Keywords: Contracepção; Adolescente; Gravidez na adolescência; Saúde sexual e reprodutiva; Contraception; Adolescent; Pregnancy in Adolescence; Sexual and Reproductive Health; CIENCIAS DA SAUDE::MEDICINA